The Process of Applying for Protection of Victims' Rights through the Witness and Victim Protection Agency (LPSK) - Aziz Hasibuan, Muhammad Anwar; Koto, Ismail (UNES Law Review, 2023)
The importance of legal protection for each community is one of the reasons for the issuance of Law Number 13/2006 on Witness and Victim Protection which was enacted on 11 August 2006. This research aims to find out, how the regulations related to victim protection in Indonesia. Then, how is the process of applying for protection of victims' rights through LPSK and finally, how is the influence of the protection provided by LPSK on victims for law enforcement. This research uses a normative method. The procedure for providing protection to witnesses and victims as regulated in Article 28 to Article 32 of Law Number 13 Year 2006 is a process that includes various procedures and requirements that must be fulfilled by witnesses and victims to be able to get protection from LPSK which is sometimes difficult for witnesses and victims. The influence of the Witness and Victim Protection Agency (LPSK) in protecting witnesses and victims has not been maximised, due to the lack of socialisation in the community, especially in the regions, about the existence of the Witness and Victim Protection Agency as an institution tasked with protecting witnesses and victims.